2019
DOI: 10.3390/cells8111385
|View full text |Cite
|
Sign up to set email alerts
|

Plant MIR167e-5p Inhibits Enterocyte Proliferation by Targeting β-Catenin

Abstract: MicroRNAs (miRNAs) are important negative regulators of genes involved in physiological and pathological processes in plants and animals. It is worth exploring whether plant miRNAs play a cross-kingdom regulatory role in animals. Herein, we found that plant MIR167e-5p regulates the proliferation of enterocytes in vitro. A porcine jejunum epithelial cell line (IPEC-J2) and a human colon carcinoma cell line (Caco-2) were treated with 0, 10, 20, and 40 pmol of synthetic 2′-O-methylated plant MIR167e-5p, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
(63 reference statements)
1
22
0
Order By: Relevance
“…Recently, numerous scientific studies have demonstrated the presence of plant miRNAs in body fluids: serum, saliva, urine, and in gastric and colon mucosa (Minutolo et al, 2018;Li et al, 2019;Link et al, 2019) and demonstrated that these circulating miRNAs might have a significant involvement in miRNA-mediated gene expression regulation. On the other hand, it has long been known that ingested RNA from food sources in nematodes and insects can control their gene expression (Whangbo and Hunter, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, numerous scientific studies have demonstrated the presence of plant miRNAs in body fluids: serum, saliva, urine, and in gastric and colon mucosa (Minutolo et al, 2018;Li et al, 2019;Link et al, 2019) and demonstrated that these circulating miRNAs might have a significant involvement in miRNA-mediated gene expression regulation. On the other hand, it has long been known that ingested RNA from food sources in nematodes and insects can control their gene expression (Whangbo and Hunter, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In exosome-like nut nanovesicles, plant miR159a and miR156c reduce the level of tumor necrosis factor (TNF) receptor superfamily member 1a (Tnfrsf1a) transcript leading to a decrease in TNF-α signaling pathway and inflammatory markers (Aquilano et al, 2019). Moreover, it was recently reported that MIR167e-5p represses intestinal cell proliferation by targeting β-catenin (Li et al, 2019). More recently, Minutolo et al demonstrated that the natural oeu-sRNAs decrease the protein expression of hsa-miR34a mRNA targets, reducing proliferation and increasing apoptosis in different tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the direct impact of plant xenomiRs on intestinal epithelial cell gene expression modulation has not been deeply addressed yet. Nevertheless, some studies have proposed that specific xenomiRs could have an impact on intestinal transporter expression or enterocyte proliferation ( 153 , 165 , 166 ), which suggests a potential role for xenomiRs in the modulation of the function of intestinal cells, including molecule absorption or intestinal barrier integrity and functionality. In this context, Fujita et al ( 165 ) reported that Caco-2 cells treated with apple exosome-like nanovesicles displayed changes in mRNA expression of several intestinal transporters including the organic-anion-transporting polypeptide (OATP2B1), whose mRNA and protein expression, along with its activity, decreased, probably by a miRNA-mediated mechanism, which potentially could modulate absorption of orally administered compounds in vivo ( 165 ).…”
Section: Insight On the Impact Of Dietary Plant Mirnas On Intestinal mentioning
confidence: 99%
“…In this context, Fujita et al ( 165 ) reported that Caco-2 cells treated with apple exosome-like nanovesicles displayed changes in mRNA expression of several intestinal transporters including the organic-anion-transporting polypeptide (OATP2B1), whose mRNA and protein expression, along with its activity, decreased, probably by a miRNA-mediated mechanism, which potentially could modulate absorption of orally administered compounds in vivo ( 165 ). It has also been reported that synthetic plant miR-167e-5p regulated the expression of Wnt/β-catenin signaling pathway key molecules, such as β-catenin and c-Myc, negatively impacting on enterocyte proliferation in vitro ( 166 ). Similar results were also observed for plant miR-156 treatment in vitro and in vivo .…”
Section: Insight On the Impact Of Dietary Plant Mirnas On Intestinal mentioning
confidence: 99%